The efficacy of interactive group psychoeducation for children with leukaemia: A randomised controlled trial. Issue 12 (December 2021) - Day, Marianne; Harris, Sally; Hussein, Deema; Saka, Mohamad Yassin; Stride, Chris; Jones, Myles; Makin, Guy; Rowe, Richard
Highlights: A psychoeducational intervention improved parent-reported quality of life for children with leukaemia. Families rated the intervention highly on improved child communication and knowledge. Group interventions may be effective but difficult to deliver for rare conditions. Abstract: Objective: To evaluate an interactive group psychoeducation programme for children treated for leukaemia. Methods: A longitudinal randomised controlled study across four UK hospitals with an immediate (N = 26) and delay control group (N = 32). The intervention covered the pathophysiology of leukaemia, its treatment, side effects and the importance of positive health behaviours. Primary outcomes were parent-reported child health related quality of life (HRQoL) and behavioural difficulties. Secondary outcomes were child-reported HRQoL, cancer-specific HRQoL, child confidence, caregiver burden, and treatment anxiety. Measures were completed pre- and immediately post-intervention, and at 13 and 26-weeks follow-up. Change over time was analysed using multilevel modelling. Acceptability questionnaires rated the intervention on benefits, recommendations, and barriers to participation. Results: The intervention significantly improved parent-reported child HRQoL but did not have a significant effect on other outcomes. Acceptability of the intervention was high. Conclusions: This study provides initial evidence that interactive group psychoeducation is acceptable to families and improves HRQoL in children with leukaemia. Difficulties with recruitment removed power to detect effect sizes that are plausible for psychoeducational interventions. Practise implications: Further studies to explore the potential of psychoeducation to improve outcomes for children with leukaemia and an examination of barriers to participation within this population are warranted.